In Absolute or Relative Terms? How Framing Prices Affects the Consumer Price Sensitivity of Health Plan Choice - Hendrik Schmitz; Nicolas R. Ziebarth (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
This paper provides fi eld evidence on (a) how price framing aff ects consumers' decision to switch health insurance plans and (b) how the price elasticity of demand for health insurance can be influenced by policymakers through simple regulatory efforts. In 2009, in order to foster competition among health insurance companies, German federal regulation required health insurance companies to express price differences between health plans in absolute Euro values rather than percentage point payroll tax differences. Using individual-level panel data, as well as aggregated health plan-level panel data, we find that the reform led to a sixfold increase in an individual's switching probability and a threefold demand elasticity increase. – – In diesem Papier zeigen wir, dass durch die Einführung des Gesundheitsfonds und der Zusatzbeiträge im Jahr 2009 die Wahrscheinlichkeit, bei einer Beitragserhöhung die Krankenkasse zu wechseln, deutlich angestiegen ist. Bis zum Jahr 2009 wurden Preisunterschiede zwischen Krankenkassen in Beitragssatzunterschieden ausgewiesen (als relative Unterschiede) während seit 2009 Preisunterschiede in absoluten Eurobeträgen dargestellt werden. Mit Daten des Sozio-oekonomischen Panels sowie aggregierten Daten ausgewählter Krankenkassen finden wir, dass diese Politikänderung zu einer stärkeren Wechselbereitschaft geführt hat und somit den Krankenkassenwettbewerb anfachen dürfte. Eine Preiserhöhung um einen Euro hat nach der Reform einen sechsmal so großen Einfluss auf die Wechselwahrscheinlichkeit wie vor der Reform.
Keywords: H51; I11; I18; 330; Health insurance; health plan switching; price competition; price elasticity; SOEP; Health insurance; health plan switching; price competition; price elasticity; SOEP